1984
DOI: 10.1038/309369a0
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus transforms precursor B cells even before immunoglobulin gene rearrangements

Abstract: The very early stages of the human B-cell differentiation pathway are poorly understood, primarily because of the lack of appropriate permanent cell lines. Epstein-Barr virus (EBV) is a putative human oncogenic virus which transforms human B cells in vitro into continuously proliferating cells. It has been believed that EBV transforms mature B cells, but recently, transformation of immature pre-B-cell lines has been reported, suggesting that EBV might also transform cells much earlier in the B-cell lineage. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 30 publications
5
49
0
1
Order By: Relevance
“…However, when corrected for CD21 -positive cells the frequency was comparable to other tissue on a per CD21-positive B cell basis. This is in agreement with other studies in which non-Ig positive marrow cells (including pre-B cells) failed to transform with EBV (18) and may explain the apparently contradictory results (15,16) demonstrating transformation of pre-B cells. The rate of transformation in foetal spleen was comparable or in some experiments higher than in adult spleen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, when corrected for CD21 -positive cells the frequency was comparable to other tissue on a per CD21-positive B cell basis. This is in agreement with other studies in which non-Ig positive marrow cells (including pre-B cells) failed to transform with EBV (18) and may explain the apparently contradictory results (15,16) demonstrating transformation of pre-B cells. The rate of transformation in foetal spleen was comparable or in some experiments higher than in adult spleen.…”
Section: Discussionsupporting
confidence: 93%
“…However, pre-B cells, which generally do not express CD21, are also reported to be transformed by EBV (15,16). Taken together with claims that other membrane antigens are important in EBV binding and infection (17), these observations motivated the present study of the correlation of EBV transformation and CD21 expression using a clonal analysis to examine actual transformation frequencies.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, whilst target cells at a number of different stages of B cell differentiation can be transformed by EBV in vitro, the cell lines so produced all display the same 'lymphoblastoid' phenotype as defined by cell surface marker analysis and growth in cell aggregates (Katamine et al, 1984;Ernberg et al, 1987;Gregory et al, 1987aGregory et al, , 1988a. In particular, such in vitro transformed lines reproducibly express high levels of the B cell activation antigens CD23, CD30, CD39 and CD70 Rowe et aL, 1985), and 0000-9420 © 1990 SGM of the cellular adhesion molecules LFA-1 (CD1 la/18), ICAM-1 (CD54), LFA-3 (CD58) (Gregory et al, 1988b) and the lymphocyte homing receptor CD44 (C. D. Gregory, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…Since there are no mature B-cells in the bone marrow of X-LA patients, X-LA derived precursor B-cells are easily immortalized from bone marrow cells by infection with EBV (Fu et al 1980; Tsuchiya et al 1983 ; Levitt et al 1984 ;Kubagawa et al 1988 ;Lau et al 1989). Development of B-cells is stopped at the same immunological stage as in the fetal liver, and we have shown that the fetal liver is also the source of normal precursor B-cells without X-LA background (Katamine et al 1984).…”
mentioning
confidence: 88%
“…Eleven control B-LCL were established from peripheral blood of healthy adults by infection with EBV and all these cell lines were immunoglobulin heavy and light chain producing mature B-cell lines. FLEB14 was an EBV induced immunoglobulin non-producing cell line derived from fetal liver, and the immunoglobulin gene was not rearranged (Katamine et al 1984). …”
Section: Establishment Of Cell Linesmentioning
confidence: 99%